SISTEM E-TRAVELING BERBASIS WEBSITE DI AET TRAVEL PT. PENJURU WISATA NEGERI: E-Traveling, UML, PHP, MySQL - Andika Saputra; Deddy Gusman; Aris Fiatno (Jurnal Inovasi Teknik Informatika, 2022)
AET Travel is one of the umrah travel agency companies that popularized direct umrah flights in Sumatra. AET Travel PT. The direction of Country Tourism is having customer order data storage using excel and only having the AET Travel system marketing via the web and there is no system for ordering tour packages or Umrah which is provided through the online system. In order to develop and continue to survive, a business entity must be supported by quality service and marketing techniques that are able to compete by utilizing networks, namely marketing via the internet. The purpose of this research is to make AET Travel PT. Across Country Tourism it is easier to manage data using a website that can be accessed easily. The research method used is the Waterfall method. And the design of this system uses the Unified Modeling Language (UML). The programming language used is PHP with Laravel Framework and MySQL database. So that in this study the Website-Based E-Traveling System at AET Travel PT. Corner Tourism Country to be more efficient.